Dampak Kontribusi Pengusaha Tani Kopi dalam Meningkatkan Pendapatan Masyarakat (Studi Kasus Desa Sumberduren Kecamatan Krucil Kabupaten Probolinggo) - Mochamad Sabiq Al Hadi; Intan Putri Nazila (Prodi Ekomoni Syariah STAI Al Akbar Surabaya, 2024)
This research is motivated by the situation in East Java, coffee plantations have become the main pillar in advancing the local economy and can increase people's income. However, many people in Sumberduren Village still sell their coffee harvest in wet logs. By looking at the abundant natural resources of coffee, especially since coffee has now become a mainstay in East Java, there is a need for innovation in product processing in order to increase the added value of coffee products and the selling price of coffee products. The problem formulation of this research is (1) What is the impact of the contribution of coffee farming in increasing the income of the people of Sumberduren Village. (2) What is the income level of the community in Sumberduren Village, Kec. Krucil, Probolinggo Regency. This research uses a qualitative type of research. The approach used in this research is a qualitative approach. This approach is a research procedure that produces descriptive data in the form of written or spoken words from organizations and behavior that is observed and directed at natural settings and individuals as a whole. Data collection techniques use observation, interviews and documentation. Data analysis was carried out using qualitative descriptive methods. The results of this research show that the contribution of coffee farming in increasing people's income in Sumberduren Village has had a broad impact. Economically, this business provides the main source of income for coffee farmers. Apart from that, the community's income is high, namely 61%. This means that the coffee farming business that the respondents are undertaking has quite a significant influence. Previously they only earned around 44% of their income, but with the contribution of coffee farming businesses in Sumberuren Village it has increased. Which is quite good. This is based on the results of interviews with farmers and other communities in Sumberduren Village, Kec. Krucil, Probolinggo Regency.